Status Kualitas Air Sungai Sekitar Lokasi Pertambangan Nikel di Kecamatan Langgikima Kabupaten Konawe Utara - Abriansyah, Abriansyah (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Langgikima Subdistrict is one of the subdistricts in North Konawe Regency, Southeast Sulawesi Province which has nickel potential so that several mining companies have invested in this area. Nickel mining activities have had both positive and negative impacts. One of the visible impacts is the decline in river water quality. One of the rivers located in Langgikima Subdistrict which is adjacent to several nickel mining locations is the Molore River in Molore Village. Determination of the water quality status of the Molore River by conducting laboratory analysis of Molore River water samples on the parameters of Physics, Chemistry, Heavy Metals, and microbiological parameters. The purpose of this study was to determine the status of water quality. The method used in this study is a purposive sampling method by using the calculation of the water pollution index at the sampling location for three consecutive months. Determination of water quality status using the pollution index method according to the Minister of Environment Decree 115/2003. Based on the results of laboratory analysis, most of the parameters are still below the required quality standards. The calculation of the Pollution Index shows that the water quality status of the Molore River is included in the lightly polluted category with a value range of 1.71-2.71. The strategy for controlling river pollution can be conducted by reducing the pollution load, namely by cooperation between the community and mining companies in managing the river environment and it is necessary to carry out good management of the sediment pond at the mining site.